2012
DOI: 10.4049/jimmunol.1103826
|View full text |Cite
|
Sign up to set email alerts
|

Immune Mechanism of the Antitumor Effects Generated by Bortezomib

Abstract: Bortezomib, a proteasome inhibitor, is a chemotherapeutic drug that is commonly used to treat a variety of human cancers. The antitumor effects of bortezomib-induced tumor cell immunogenicity have not been fully delineated. In this study, we examined the generation of immune-mediated antitumor effects in response to treatment by bortezomib in a murine ovarian tumor model. We observed that tumor-bearing mice that were treated with bortezomib had CD8+ T cell-mediated inhibition of tumor growth. Furthermore, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 50 publications
1
46
0
Order By: Relevance
“…7,11,22 Recently, wogonininduced early apoptotic ecto-CRT (Table 1) was also found to be mediated by PERK and PI3K. 58 Hence, in spite of this plasticity, the reliance of several ICD inducers on the ER stress sensor PERK as central 'DAMP-trafficking master' is noteworthy. Whether this is related to the archetypical induction of a viral response in the target cell (as described above), requiring the interface between PKR-mediated IFN response and PERK as ER stress sensor, 59,60 needs to be further explored.…”
Section: The Plasticity and Regulation Of Danger Signalling And Sensingmentioning
confidence: 99%
“…7,11,22 Recently, wogonininduced early apoptotic ecto-CRT (Table 1) was also found to be mediated by PERK and PI3K. 58 Hence, in spite of this plasticity, the reliance of several ICD inducers on the ER stress sensor PERK as central 'DAMP-trafficking master' is noteworthy. Whether this is related to the archetypical induction of a viral response in the target cell (as described above), requiring the interface between PKR-mediated IFN response and PERK as ER stress sensor, 59,60 needs to be further explored.…”
Section: The Plasticity and Regulation Of Danger Signalling And Sensingmentioning
confidence: 99%
“…Other mechanisms of action by which bortezomib may kill cancer cells are through ER-stress and activation of the unfolded protein response (UPR) (57) and triggering apoptosis by preventing the degradation of pro-apoptotic proteins (56, 58). Some studies have shown that treatment of cancer cells using bortezomib increases surface expression of Hsp90 and Hsp60 in cancer cells leading to their more effective phagocytosis by dendritic cells (DCs), improving tumor vaccine effects (59). Bortezomib-treated mice also exhibit increased DC maturation and phagocytic potential (59).…”
Section: Standard Chemotherapeutic Drugs That Boost Ov Activity Throumentioning
confidence: 99%
“…Some studies have shown that treatment of cancer cells using bortezomib increases surface expression of Hsp90 and Hsp60 in cancer cells leading to their more effective phagocytosis by dendritic cells (DCs), improving tumor vaccine effects (59). Bortezomib-treated mice also exhibit increased DC maturation and phagocytic potential (59). On the other hand, one study found that bortezomib treatment leads to apoptosis of allo-reactive CD4+ T-cells.…”
Section: Standard Chemotherapeutic Drugs That Boost Ov Activity Throumentioning
confidence: 99%
“…The combination of arsenic and all-trans-retinoic acid is used against PML-RARα, and can modulate antigen presentation [129]. Bortezomib, an agent used for multiple myeloma that targets the proteasome and NF-κB, can affect numbers of CD8 + T cells and dendritic cells [130]. Erlotinib, a successful non-small cell lung cancer therapeutic that targets EGFR, can also induce an influx of dendritic cells [131].…”
Section: Targeted Oncogene Inactivation and Immune Response In Human mentioning
confidence: 99%